THE INFLUENCE OF SERVICE QUALITY AND TRUST ON USING CUSTOMER SATISFACTION DELIVERY SERVICES AND ITS IMPACT ON CUSTOMER LOYALTY (Case Study on JNE Sei Rampah) - CAI CEN, CIA (International Conference on Health Science, Green Economics, Educational Review and Technology, 2020)
This study aims to determine the effect of service quality and trust on consumer satisfaction using freight forwarding services and their impact on customer loyalty. The population in the study were employees who worked at a significant level of alpha = 5 %. The data from the study were processed using the help of the SPSS program version 25.00 for windows. Based on the results of the study, in the multiple linear regression test, the regression equation was obtained as follows: equation I: Z = 13.850 + 0.072 X1 – 0.216 X2, while equation II: Y = 25.047 – 0.197 X1 – 0.256 X2 + 0.341Z. The results of hypothesis testing using multiple linear regression analysis and t test, which showed that the first hypothesis was rejected, meaning that in explaining the Quality of Service variable (X1) it had no effect on the Customer Loyalty variable (Z),